Running versus strength-based warm-up: acute effects on isometric knee extension function - Girard, O.; Carbonnel, Y.; Candau, R.; Millet, G. (European Journal of Applied Physiology, 2009)
This study investigated the influence of two warm-up protocols on neural and contractile parameters of knee extensors. A series of neuromuscular tests including voluntary and electrically evoked contractions were performed before and after running- (R WU; slow running, athletic drills, and sprints) and strength-based (S WU; bilateral 90° back squats, Olympic lifting movements and reactivity exercises) warm ups (duration ~40 min) in ten-trained subjects. The estimated overall mechanical work was comparable between protocols. Maximal voluntary contraction torque (+15.6%; P < 0.01 and +10.9%; P < 0.05) and muscle activation (+10.9 and +12.9%; P < 0.05) increased to the same extent after R WU and S WU, respectively. Both protocols caused a significant shortening of time to contract (-12.8 and -11.8% after R WU and S WU; P < 0.05), while the other twitch parameters did not change significantly. Running- and strength-based warm ups induce similar increase in knee extensors force-generating capacity by improving the muscle activation. Both protocols have similar effects on M-wave and isometric twitch characteristics.